The relationship between state's revenues and expenditures in Malaysia: some robust results - Habibullah, Muzafar Shah; Abd. Ghani, Judhiana; Abdullah, Asna Atqa; Zaharuddin, Zati Aqmar (Universiti Putra Malaysia, 2025)
This study focuses on the intertemporal dynamics between revenues and expenditures, as well as the strategies used by state governments in managing their public deficits. This study provides an opportunity to explore several hypotheses to investigate the Malaysian government's tax collection and spending behavior. The tax-spend hypothesis posits that governments generate tax revenues prior to initiating new expenditures. In contrast, the spend-tax hypothesis posits that governments first engage in spending activities and afterwards augment tax receipts in order to fund their expenditures. Another concept that exists is the fiscal synchronization hypothesis, which posits that governments make choices about both revenues and spending concurrently. Choices pertaining to expenditure and the generation of income may allow for autonomy. Based on an empirical investigation conducted on yearly data including revenue and expenditure in 13 Malaysian states from 1990 to 2018, the findings derived from our Granger long-run causality, as corrected by the error-correction framework provide consistent results that support the fiscal synchronization hypothesis. © (2025), (Universiti Putra Malaysia). All rights reserved.